Teaching Computational Thinking to Middle School Students using Rubik’s Cube - Quintela, Barbara M.; Esteves, Lara O.; Campos, Julia de Paula; Verly, Ana Clara; Oliveira, Alessandreia (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2025: Anais do V Simpósio Brasileiro de Educação em ComputaçãoDO - 10.5753/educomp.2025.5329, 2025)
The present work describes the implementation of an activity aimed at teaching the main concepts of Computational Thinking to children starting in middle school. The primary concepts addressed are Decomposition and the use of Algorithms to solve the first face of a standard 3x3x3 Rubik’s Cube using the daisy method. The activity was conducted with two groups of 20 students during 40-minute sessions. It is discussed that, depending on prior experience with the cube, this time might not be sufficient. Results indicate that solving the cube was a dynamic activity that engaged students and helped participants understand the importance of sequence and order in the steps to be followed.